Resisting militarism : direct action and the politics of subversion - Rossdale, Chris (Advances in critical military studies., 2019)
This book explores why anti-militarists resist, considers the politics of different tactics and examines the tensions and debates within the movement. It argues that anti-militarists can help us understand militarism in new and useful ways, and that that the methods of anti-militarists can be a potent force for radical political change.